A novel size-based method for assessing the spawning potential ratio of data-poor octopus fisheries - Prince, Jeremy D.; Rufiati, Indah; Septiani, Wahyu Dita; Kembaren, Duranta Diandria; Gough, Charlotte Louise Anne (Frontiers in Marine Science, 2025)
Cephalopod biology, which is characaterised by short lifespans, semelparous reproduction, rapid non-asymptotic growth, and seasonally fluctuating biomass, presents a particular challenge stock assessment. Small scale, data-poor artisanal octopus fisheries are an increasingly important source of food and income for coastal fishing communities but pose a particularly pernicious assessment challenge. We developed and tested a novel size-based data-poor assessment methodology, demonstrating its applicability with 17 Indonesian fisheries for Octopus cyanea. The Short-Lived Assessment Model (SLAM) is similar to Length-based Spawning Potential Ratio Assessment (LBSPR) and Length-based Integrated Mixed Effects (LIME) methodologies, in assuming that taxa share both growth curves and a relativity between maximum size and size of maturity. Incorporating a power curve form of growth typical of cephalopods and monthly time steps SLAM estimates selectivity at age schedules, monthly fishing mortality rates (F) and spawning potential ratio (SPR). A minimum of 12 monthly samples of catch at weight data (CAW) are required, but longer time series and additional indices of effort and/or catch will produce more reliable results. SLAM’s structure is flexible; with <24 months of CAW it parallels LBSPR in assuming equilibrium dynamics and constant monthly recruitment. With >24 months of CAW, a dynamic structure becomes possible similar to LIME, and seasonal recruitment patterns can be estimated.